2023
DOI: 10.1002/uog.26283
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis and postnatal outcome of fetal congenital knee dislocation: systematic review of literature

P. I. Cavoretto,
M. Castoldi,
G. Corbella
et al.

Abstract: ObjectivesCongenital Knee Dislocation (CKD) or Genu Recurvatum is a rare condition affecting 1 over 100,000 newborns, characterized by anterior hyperextension of the knee joint, increased transverse skin folds over the anterior surface of the knee and prominence of femoral condyles into the popliteal fossa. Prenatal diagnosis is poorly described in the literature and challenging, especially when it appears isolated and not in the context of polymalformative or syndromic patterns. The purpose of this study is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Prenatal diagnosis of CDK is challenging, as it is often undetected by ultrasound. In a recent review of 20 cases of CDK detected by prenatal ultrasound, the median gestational age at diagnosis was 20 weeks (range, 14–38 weeks) [ 12 ]. A 3-dimensional (3-D) with a real-time 3-D (4-dimensional) ultrasonographic evaluation seems advantageous, as it offers a more dynamic interpretation of the limb position and mobility [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal diagnosis of CDK is challenging, as it is often undetected by ultrasound. In a recent review of 20 cases of CDK detected by prenatal ultrasound, the median gestational age at diagnosis was 20 weeks (range, 14–38 weeks) [ 12 ]. A 3-dimensional (3-D) with a real-time 3-D (4-dimensional) ultrasonographic evaluation seems advantageous, as it offers a more dynamic interpretation of the limb position and mobility [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that isolated CDK is a rare anomaly, and most isolated cases exhibit a favorable prognosis, with excellent motor function of the lower limbs and ambulatory ability. Conversely, complex cases involving genetic syndromes or multiple anomalies generally have poor prognoses [ 18 20 ]. Moreover, there is a tendency for numerous malformations accompanied by developmental abnormalities affecting the upper extremities, face, digestive tract, and reproductive system.…”
Section: Discussionmentioning
confidence: 99%
“…Before birth, the diagnosis can be confirmed through prenatal 3D or 4D ultrasound, typically performed around the 20th week of gestation [ 3 ]. By employing prenatal diagnosis, swiftly referring to adept pediatric orthopedic surgeons, and initiating early conservative treatment, the necessity of surgery can be significantly reduced and the efficacy of the treatment enhanced [ 18 ]. Following birth, the diagnosis is typically confirmed based on observing distinctive deformities, a physical examination, and conventional knee X-rays [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor prognostic factors include an associated syndrome, knee flexion <50% and absence of an anterior skin groove 5. In cases of isolated congenital knee dislocation, the outlook for motor function of the lower limbs and ambulation is excellent 6…”
mentioning
confidence: 99%